Crescendo Model of Career Motivation and Commitment: Identity, Insight, and Resilience - King, Albert S. (International journal of value-based management, 1999)
This paper provides an experiential exercise to increase understanding of employees' career motivation and commitment and its relation to employees' perception of identity, insight, and resilience. Three separate conditions influencing employee attraction to career orientation are self-identity, insight, and resilience. These three component dimensions of employee career motivation are outlined and used to define an eight-phase crescendo model through which individuals tend to pass in their decision to form an affective career commitment. The analysis supports the notion of a stepwise movement from identity to insight to resilience in strengthening employees' career motivation and demonstrates how progressive phases are associated with career commitment. Although the levels and phases are progressively prepotent and valenced in predicting employee propensity to form an enduring career commitment, different patterns and paths through the phases for individuals are indicated.